Monetary policy and the gender and racial employment dynamics in Brazil - Patricia Couto; Clara Brenck (Levy Economics Institute of Bard College, 2023)
Monetary policy has been historically concerned with controlling inflation, using the interest rate as its main tool. However, such policies are not gender- or race-neutral. This paper explores econometrically the effect of changes in the interest rate for female and black employment creation in Brazil. We conduct a panel data fixed effects analysis for 13 states between 2012 and 2021 to estimate the effects of changes in interest rates on unemployment, separating the data by gender and race. Our results show that the real interest rate has a positive effect on the relative unemployment of black men to white men, no effect on the relative unemployment of black women to white men, and a negative effect on the relative unemployment of white women to white men. These effects are intensified in regions where the black population ratio is lower. This paper contributes to understanding the challenges to closing gender and racial gaps, particularly in developing economies. We conclude that social stratification, if not considered, can lead to misleading policies that perpetuate unequal socioeconomic outcomes.
Keywords: B54; E24; E52; E58; 330; Monetary policy; gender inequality; racial inequality; social stratification